Perlindungan Hukum Bagi Karyawan Giant Supermarket Sebagai Korban Pemutusan Hubungan Kerja - Tambunan, Joy Catherine Carina; Wahdah, Azzhara Nikita; A, Annisa; Prawira, Rio Nusa (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Legal protection for employees affected by layoffs is important. Termination of employment has a big impact on employee welfare, especially for those who work in large companies like Giant. In this research, there is a formulation of the problem that will be discussed, namely (1) The concept of legal protection for employees who experience termination of employment (PHK) by the company when viewed from the case of layoffs of Giant Supermarket employees; (2) The form of settlement provided by law and its implementation in the case. The aim of this research is to find out the concept of legal protection for employees affected by layoffs and what the form of resolution is in law and implementation in related cases. This research uses a normative method that is guided by legal norms, legal principles, and positive Indonesian law relating to employment law. From this research, the results obtained are (1) This labor law can create regulations that force employers to comply and are obliged to guarantee the welfare of their workers. Regulations regarding layoffs can be found in the twelfth chapter of the Employment Law in Articles 150 to 172, totaling 18 articles. Meanwhile, in Part Five of the Job Creation PERPU, provisions regarding termination of employment are regulated in Articles 151, 151A, 153, 154A, 156, 157, 157A, and 160; (2) Based on Article 151 paragraph (2) Legal protection, namely legal protection that is preventative (preventive) and law enforcement (repressive). Employers are obliged to inform workers/labor unions of their intentions and reasons for layoffs before they are carried out.